Sago Extract Enterprise / Fairul Azuan B. Abd. Zaim...[et al.] - Abd Zaim, Fairul Azuan; Kasua, Mohd Ajam; Awang, Siti Nazirah; Suratman, Nur Othman (Faculty of Plantation & Agrotechnology, 2010)
The Sago palm (Afetrmylon sagu Rottb.) has been known in trade in South East Asia for at least 700 years. According to Berkill ( 1966), sago was ,mentioned by Chinese writers in the 12th Century. It is a hapaxanthic (once flowering) and soboliferous (suckering) feather-leaf palm which accumulates starch in its trunk during its vegetative phase of growth. Most of the several species of starch producing palm, Metroxylon sagu is by far the most important palm exploited commercially for starch production. Sago palm belongs to the family Palmae Jussieu, subfamily Calamoideae Griffith, tribe Calameae Drude, subtribe Metroxylinae Blume and genus Metroxylon Rottboell (Uhl and Dransfield 1987). This palm can reach a length of 6-16 m and has approximately 24 leaves or fronds. It is often cultivated and grows well in freshwater swamps. The higher the number of the crown carries, the larger the diameter of the trunk. Each month, one new frond appears out of the growing point. and the oldest one dies. The one of the most popular product from Sago palm is starch food called Kepurung or Ambuyat. This food is known widely in Beaufort. Kuala Penyu, Sipitang, Kota Belud area and moderately interest at Tawau, Sandakan and Lahad Datu. The home made Kepurung and Ambuyat had been eaten so Jong as the sources of energy substituting the rice. ln addition, sago's is now can be a great ingredient of noodles, Vermicelli (bee hoon), biscuits and many other foods. Some are used as feed stuffs for animal and livestock, pulp and paper industries. One hundred grams of dry sago yields contain 355g calories, an average of 94 g of carbohydrate, 0.2 g of protein, 0.5 g of dietary fiber, IO mg of calcium, 1.2 mg of iron, and negligible amounts of fat, carotene, thiamine, and ascorbic acid. In recent research at Universiti Sarawak (UniMas), the sago's can be produce as Biopetroleum and diesel replacing fossil fuel that already exist right now. Thus, this new discovery attracted many intention of local and foreign investor to invest more on this experiment. As are result, our group totally agrees to run this project as our entrepreneurs' project on the name of Urban Sago Extract Enterprise.